Rhetoric and the familiar in Francis Bacon and John Donne - Derrin, Daniel, 1980- (Fairleigh Dickinson University Press ; Co-published with The Rowman and Littlefield Publishing Group, Incorporated, 2013)
Rhetoric and the Familiar examines the rhetorical practice of Francis Bacon and John Donne in both their writing and public speaking. It explores how their rhetorical planning negotiates the need both to use and combat familiar ideas, images, and emotions, when engaging different audiences. The book's main selling points are that it explores well-known texts from the neglected angle of faculty psychology. Its ability to illuminate familiar ground in an important but neglected way will be its main selling point in the academic market.